Survey on household energy consumption of public apartments in Bandung City, Indonesia - Usep Surahman; Johar Maknun; Erna Krisnanto (IPTEK Journal of Proceedings Series, 2017)
Indonesia has been experiencing population and high economic growth in line with rapid urbanization. As a consequence, the needs for living areas increased faster and enormous number of residential buildings, especially apartments, have been developed in major cities, such as Bandung, resulting in further growth of energy consumption.Thus, it is necessary to develop energy-saving sustainable apartments in Indonesia in order to cope with escalating energy issues.  This paper reveals the detailed profiles of household energy consumption of apartments in Bandung City, Indonesia. A survey within the city was conducted (n=100) in 2016 to obtain household energy consumption data of public apartments. The detailed information about household appliances and domestic energy consumption profile among households were investigated through the face-to-face interviews and the measurement of appliances’ capacities by using the watt checker. The annual average energy consumption including electricity and gas was calculated. The results show that the annual average operational energy for public apartments are 9.8 GJ/year. The annual average energy for cooking accounts for the largest percentage (48%) of operational energy followed by refrigerator (27%), lighting (10%), entertainment (9%), cooling (3%), etc. The profiles of CO2 emissions are similar with those of energy and the potential energy-saving strategies for apartments in Indonesia were proposed.